PENGARUH PENERAPAN METODE BERCERITA TERHADAP PERKEMBANGAN PERILAKU MORAL ANAK DIDIK DI TK NUR ILMI JUPPAI - Muin, Kasniar; Muharram, Muharram; Sunarty, Kustiah; Zainuddin, M. Said (Universitas Borneo Tarakan, 2023)
This research aims to determine whether the method of narrative influences the development of student behavior at Kindergarten Nur Ilmi Juppai, Barru Regency. The research method used is quasi-experimental with a quantitative approach and employing the pretest posttest control group design. The research population consists of all students in class B, comprising a total of two classes. The research sample is class B1, serving as the experimental group with a total of 20 students, and class B2, serving as the control group with a total of 18 students. The techniques employed for data collection are observation and checklists. The techniques used for data analysis are descriptive and inferential. The results of the analysis on the homogeneity test of the experimental class obtained a higher value of 0.67 compared to the control class, which had a value of 0.15. It can be observed that the results of the test on the development of moral behavior among students have improved after implementing the storytelling method without the use of props, achieving an average mastery score in the very good category. Based on the data analysis results, it can be concluded that there is an impact of the storytelling method using visual aids on the students at Kindergarten Nur Ilmi Juppai, Barru Regency